Kiki's delivery service [videorecording (DVD)] - Miyazaki, Hayao, 1941-; Dunst, Kirsten, 1982-; Hartman, Phil; Reynolds, Debbie; Kadono, Eiko
On her 13th birthday, a young witch named Kiki must fly away from home to a new city to find her niche in life. Accompanied by her chatty cat, Jiji, she starts a flying service and discovers lots of fun-filled escapades and meets plenty of new friends.